(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article talks about the skill of the critic, sincerity in creativity, criticism, purpose and harmony in the creativity of the critic and the creator. In addition, it reveals the skill of creating a character in a work of art. A brief analysis of prose works of the 20th century and critical opinions about the writer’s skill are described.